Doses de nitrogênio em Brachiaria brizantha cv. Marandu : alterações nos indicadores de qualidade do solo - Ceni, Isabela de (2018)
ABSTRACT:The use of nitrogen fertilizers increases the dry matter yield of forages and causes alterations in the chemical and microbiological characteristics of the soil. In this way, the objective was to evaluate the changes in soil quality indicators cultivated with Brachiariabrizantha cv. Marandu, as a function of nitrogen doses: 0, 25, 50, 75 and 100 kg N ha-1 cut-1, using as the source of N ammonium sulfate. The cuttings were performed when the forage reached the height of 0.40 m, respecting the height of residue of 0.20 m. The experimental design was a completely randomized design with five replicates. Soil samples were collected at a depth of 0.00-0.20 m in the years 2016 and 2017, in the months of May and November. The soil quality indicators were: pH, microbial biomass carbon (C-BM), microbial biomass nitrogen (N-BM), basal respiration (C-CO2), metabolic quotient (qCO2), microbial quotient , urease, β- glucosidase and C: N ratio. The results obtained were that the increase of nitrogen reduced soil pH, leading to a reduction in C-BM and qCmic and an increase in C-CO2, qCO2, urease and NMP Azos.